NOTES ABOUT THE COMPLEXITY IN PSYCHOLOGY - Mateo García, Miguel Ángel (Anales de Psicología / Annals of Psychology, 2003)
This paper presents some hints on complexity, such as this concept has ever been treated by western science. A special stress is posed in its newest conception in terms of nonlinearity, and it is noticed the core role played by the geometric-topologic notion of reality. Moreover, it is shown as this state-of-facts has deep consequences for Psychology. Human psychological development and behaviour, normal and pathological, can be thought of as beeing complex, dynamical, open, and self-organized systems. According to this point of view, dynamical systems theory is proposed as the most appropriate frame for building a right methodology for Psychology. Even at its most verbal-conceptual level, dynamical systems theory offers Psychology, at least (but not last), invaluable possibilities for reformulating important ideas as a source of relevant hypothesis for our science to advance.